2008
DOI: 10.1254/jphs.08028fp
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Histamine Signaling by Probiotic Lac-B: a Possible Mechanism of Its Anti-allergic Effect

Abstract: Abstract. It has been shown that probiotic bacteria are effective for the treatment of allergic diseases. As histamine plays a central role in allergic diseases, it is possible that probiotic bacteria affect the allergy-related histamine signaling. Here, we investigated the effect of Lac-B, a mixture of freeze-dried Bifidobacterium infantis and Bifidobacterium longum, on the allergyrelated histamine signaling. In the nasal allergy model rats made by sensitization and provocation with toluene 2,4-diisocyanate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 33 publications
(19 reference statements)
3
38
0
1
Order By: Relevance
“…Additionally, TDI-sensitized rats also display many of the characteristic features of AR in humans, including infiltration of eosinophils and mast cells (40), increase in the level of cytokines (8,(41)(42)(43), elevation of H1R mRNA and protein level (12), increase in the HDC mRNA level, HDC activity, and histamine content (13), even though histamine release was triggered by neuropeptide, but not IgE, in TDI-sensitized animals. Furthermore, the expression of IL-4 and IL-5 mRNAs was also up-regulated in the nasal mucosa of TDI-sensitized rats after provocation with TDI (16,17). Therefore, we consider that TDI-sensitized rats can be a model of AR.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, TDI-sensitized rats also display many of the characteristic features of AR in humans, including infiltration of eosinophils and mast cells (40), increase in the level of cytokines (8,(41)(42)(43), elevation of H1R mRNA and protein level (12), increase in the HDC mRNA level, HDC activity, and histamine content (13), even though histamine release was triggered by neuropeptide, but not IgE, in TDI-sensitized animals. Furthermore, the expression of IL-4 and IL-5 mRNAs was also up-regulated in the nasal mucosa of TDI-sensitized rats after provocation with TDI (16,17). Therefore, we consider that TDI-sensitized rats can be a model of AR.…”
Section: Discussionmentioning
confidence: 93%
“…Among them, IL-4 plays a central role in allergic inflammation: it is associated with the development of T lymphocytes, acts as a growth factor for Th2 cells, stimulates IgE synthesis, and is involved in mast cell activation (15). Previous reports that the expression of IL-4 and IL-5 mRNAs was up-regulated in nasal mucosa suggest the involvement of these cytokines in nasal hyperresponsiveness in TDI-sensitized rats (16,17).…”
Section: A Llergic Rhinitis (Ar)mentioning
confidence: 99%
“…The H1R expression level is highly correlated to the severity of allergic symptoms, and compounds that suppress H1R gene expression alleviate allergic symptoms (12)(13)(14)(15)(16). Therefore, drugs targeting the proteins that compose the signaling pathway involved in histamine-induced up-regulation of H1R gene expression could be good therapeutics for allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of H1R signaling depends on the H1R expression level (8). Our recent studies have demonstrated that the level of H1R gene expression is strongly correlated with the severity of allergic symptoms in model rats and patients with pollinosis (9,10), and compounds that suppress H1R gene up-regulation alleviate allergic symptoms (11)(12)(13)(14)(15)(16). These findings suggest that the H1R gene is an allergy-sensitive gene, i.e.…”
mentioning
confidence: 98%
“…Both cytokines are TH2-derived, with IL-4 acting on Bcells to induce class-switching and on mast cells to induce degranulation and further cytokine production and IL-5 inducing eosinophil degranulation. Specific strains found to inhibit IL-4 and IL-5 production include L. casei (Schiffer et al, 2009), L. rhamnosus (Ghadimi et al, 2008), B. longum (Takahashi et al, 2006) and B. infantis (Dev et al, 2008).…”
Section: Discussionmentioning
confidence: 99%